In-vitro inhibition of IFNγ+ iTreg mediated by monoclonal antibodies against cell surface determinants essential for iTreg function - Daniel, Volker; Sadeghi, Mahmoud; Wang, Haihao; Opelz, Gerhard (BMC immunology, 2012)
Background: IFNγ-producing CD4+CD25+Foxp3+ PBL represent a subtype of iTreg that are associated with good long-term graft outcome in renal transplant recipients and suppress alloresponses in-vitro. To study the mechanism of immunosuppression, we attempted to block cell surface receptors and thereby inhibited the function of this iTreg subset in-vitro using monoclonal antibodies and recombinant proteins.Methods: PBL of healthy control individuals were stimulated polyclonally in-vitro in the presence of monoclonal antibodies or recombinant proteins against/of CD178, CD152, CD279, CD28, CD95, and HLA-DR. Induction of IFNγ+ iTreg and proliferation of effector cells was determined using four-color fluorescence flow cytometry. Blockade of iTreg function was analyzed using polyclonally stimulated co-cultures with separated CD4+CD25+CD127-IFNγ+ PBL. Results: High monoclonal antibody concentrations inhibited the induction of CD4+CD25+Foxp3+IFNγ+ PBL (anti-CD152, anti-CD279, anti-CD95: p < 0.05) and CD4+CD25+CD127-IFNγ+ PBL (anti-CD178, anti-CD152, anti-CD279, anti-CD95: p < 0.05). Effector cell proliferation increased with increasing antibody concentrations in culture medium (anti-CD178 and anti-CD279: p < 0.05). Conversely, high concentrations of recombinant proteins induced formation of CD4+CD25+Foxp3+IFNγ+ PBL (rCD152 and rCD95: p < 0.05) and decreased cell proliferation dose-dependently (rCD178 and rCD95: p < 0.05). Our data suggest an inverse association of iTreg induction with effector cell proliferation in cell culture which is dependent on the concentration of monoclonal antibodies against iTreg surface determinants. 3-day co-cultures of polyclonally stimulated PBL with separated CD4+CD25+CD127-IFNγ+ PBL showed lower cell proliferation than co-cultures with CD4+CD25+CD127-IFNγ- PBL (p < 0.05). Cell proliferation increased strongly in CD4+CD25+CD127-IFNγ- PBL-containing co-cultures in the presence of monoclonal antibody (anti-CD28, anti-CD152, anti-CD279: p < 0.05) but remained low in co-cultures with CD4+CD25+CD127-IFNγ+ PBL (with the exception anti-CD28 monoclonal antibody: p < 0.05). Monoclonal antibodies prevent iTreg induction in co-cultures with CD4+CD25+CD127-IFNγ- PBL but do not efficiently block suppressive iTreg function in co-cultures with CD4+CD25+CD127-IFNγ+ PBL. Conclusions: CD178, CD152, CD279, CD28, CD95, and HLA-DR determinants are important for induction and suppressive function of IFNγ+ iTreg.